Antioxidant enzymes responses of polychaete Perinereis aibuhitensis following chronic exposure to 17β-estradiol. Issue 3 (2nd July 2016) - Lv, Linlan; Dong, Xuexing; Lv, Fu; Yu, Yebin; Zhao, Weihong; Liu, Fei
Abstract: The occurrence of 17β-estradiol (E2) in the aquatic environment can lead to damage to the reproductive system, along with other adverse effects including oxidative stress, in aquatic organisms. In the present study, Perinereis aibuhitensis were treated with E2 at 0.1, 1, 10, 100 and 1000 μg/L for 205 d, after which the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione- S -transferase (GST), and the concentrations of glutathione antioxidant biomarker responses were studied. Weight gain and specific growth rate of P. aibuhitensis were not significantly affected by E2 treatment. Although no significant differences in mortality were observed, the group receiving the highest dose of E2 (1000 μg/L) experienced the highest rate of mortality. Treatment with E2 enhanced the levels of total glutathione (T-GSH), but levels of glutathione reduced (GSH) were significantly decreased by 17.02, 20.55, 23.45, 31.91 and 56.08%, with a concomitant increase in the levels of glutathione disulphide (GSSG) by 148.58, 213.05, 232.62, 294.63 and 306.45%, at 0.1, 1, 10, 100 and 1000 μg/L E2, respectively. The redox ratio of GSH/GSSG was significantly decreased ( p < 0.01). The results of this study suggest that long-term exposure of P. aibuhitensis to E2 may inhibit antioxidant enzyme activities, thereby reducing the capacity of its detoxification system.